Análisis del uso y abuso de las medidas de protección, otorgadas en los casos de violencia intrafamiliar, como garantía del derecho a la defensa y seguridad jurídica de los sujetos en conflicto. - Fuertes, Gabriel E. (2022)
This project contains an important proposal and its utmost relevance, by virtue of that from the professional experience of the authors of this work, as public officials of justice operators, such as the Attorney General's Office State and the Judicial Function, it has been possible to show that there is a lack of effectiveness protection mechanisms, granted in cases of domestic violence, unleashing at a certain time and extent, in an abuse of them, taking into account note that what is determined by the Comprehensive Organic Criminal Code (2014), as well as also the Law to prevent and eradicate violence against women, implemented to guarantee and promote the rights of women to a life free from violence, could be infringing the rights of the alleged aggressor, hence the need to carry to carry out regulations that allow regulating the use of protection mechanisms, that according to our internal legislation, are determined in Article 558 of the Code Organic Comprehensive Penal Code, which would commit the State to work comprehensively on the attention that should be given to the people who make up the family nucleus, from the perspective of the complainant, the defendant and the members of the family nucleus, which is fully related to what is determined in art. 78 of the CRE, trying to guarantee that there is legally a balance between the procedural subjects that are part of a conflict, for which the monitoring and regulation of the use of the tickets is decisive. assistance, and in the event that misuse is evidenced, render them null and void and penalize whoever misuses them, that is far from the nature for which they were granted.